Integrating TOGAF 10 and ISO 20000-1:2018 for Digital Multi-finance Service Level Agreement/Mean Time to Repair improvements - Bagus Resa Destian; Panca Dewi Pamungkasari (Green Intelligent Systems and Applications, 2026)
Digital transformation in the multi-finance sector demands service architectures that are flexible, reliable, and scalable; however, misalignment between architectural design and operational execution often leads to weak service performance. This study proposes an integrated framework that combines TOGAF 10 artifacts with ISO/IEC 20000-1:2018 processes to systematically estimate Service Level Agreement (SLA) targets and reduce Mean Time to Repair (MTTR). Using a Design Science Research approach, the framework was implemented in a 14-month case study at PT XYZ Multi-finance. The resulting artifacts include a bidirectional traceability model linking business objectives to SLA and MTTR indicators, as well as an operability pattern catalog to support “design for operability.” The implementation delivered measurable operational improvements: MTTR decreased from a peak of 775 minutes to below 60 minutes, Mean Time to Detect (MTTD) was reduced by approximately 90%, SLA compliance increased to 99.7%, and incidents caused by manual configuration errors declined. These results demonstrate that integrating enterprise architecture design with service management processes can significantly improve service reliability and overall operational performance.